The Influence of Price, Quality, and Location on Purchasing Decisions at TJA Tech Second-Hand Laptop Store Kediri - Pramesthi, Luri Julia Puput; Ratnanto, Sigit (Proceeding Kilisuci International Conference on Economic & Business, 2025)
Research aim : This research study seks to examine how price, quality and location influence the decision-making process of consumers purchasing second-hand laptop at TJA Tech Kediri Design/Methode/Approach : This research employs a quantitative approach with a casual design. The target of this research includs consumers who have bought second-hand laptops from TJA Tech Kediri. The study’s sample consist of 40 respondents,  chosen through a questionnaries. The method of data analysis applied in this research ismultiple linear regression. Research Finding : The outcomes of this research reveal that pricing and quality exert a otable influence, while location does not significantly affect the buying decision at TJA Tech Second-Hand Laptop Store in Kediri. Theoretical contribution/Originality : It holds a significant impact on the consumer’s decision-making process. This study investigates the intricate connection among these three factors analyzing the manner in which  their interactions shape consumer preferences and influence customer buying choices.. Practitionel/Policy implication : The research offers practical insights for TJA Tech Kediri to enhance purchasing decisions by considering price, quality, and location in their marketing strategy, as well as increasing sales volume. Research limitation : This study only discusses three main variables: price, quality, and location. Other factors that may also influence purchasing decisions, such as promotions or services, are not covered in this study.